Silsilah Raja-Raja Keturunan Bugis dalam Hikayat Bugis-Melayu - Kasma F Amin (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2017)
Abstract This study was conducted to trace the historical narratives about the relationships in of Bugis people who were travelling a settling somw where with some Asian trible recorded in the classical literary words. The aims of this research was find out a clear line of family tree of of the kings of Buginess kings their main roles of in the inter-ethnics peace. The Hikayat Bugis-Malay stories relating to kingdoms, of B indicated to have relations in some tribes in Nusantara (courtelly Asean) with the Bugis travellers. Some tribes mentioned in the hikayat setting in same islands such as Riau, Aceh, Siak, Johor, Pahang, Langkawi, Java, Melaka, and Kanboja. The benefits gained from this study thas theoretical and practical benefits. The writing method was tescriptive qualitve with ethnometodology approach which was based literature philology. The through study of the Bugis-Malay Hikayat, the close relation of tribes in Asia cab be described, for example socio-politics, relations, peace, marriage, trade wich then led to bonding through out family trees.